Consumer Based Competitive Priorities of Via Tuban Shrimp Paste in the Indonesian Market: An Importance Performance Analysis: Prioritas Kompetitif Berbasis Konsumen dari Terasi Udang Via Tuban di Pasar Indonesia: Analisis Kepentingan-Kinerja - Mahmudah Enny Widyaningrum; Andre Ridho Saputro; Eka Saputra; Diana Evawati; Muslichah Erma Widiana; Yoga Adi Prayogi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study evaluates the consumer-based competitive priorities of Via Tuban shrimp paste (terasi) by analyzing the gap between perceived importance and performance of key product attributes using Importance–Performance Analysis (IPA). Drawing on the resource-based view and consumer value theory, the research assesses seven attributes; quality, packaging, price, distribution, brand image, food safety, and promotion & innovation through a structured 5-point Likert survey administered to 65 purposively selected consumers. Findings reveal a significant shortfall in performance relative to expectations, with a grand mean importance of 4.26 and performance of 2.63. All attributes show negative gaps; "quality" has the largest gap (−1.81) and falls into Quadrant I (high importance–low performance), marking it as the top priority for improvement. "Packaging," "distribution," and "food safety" fall into Quadrant II (high importance–high performance), indicating existing strengths. In contrast, "price" and "promotion & innovation" are lower priorities, while "brand image" suggests possible overemphasis. The study provides a clear, evidence-based roadmap for capability upgrading in traditional fermented seafood MSMEs and contributes to the strategic management of local food products by linking customer perception to actionable operational improvements. Limitations include a localized sample and reliance on self-reported data, suggesting opportunities for future research expansion.